Combined lensed estimator to probe the post-reionization H i power spectrum - Arora U.; Dutta P. (My University, 2025)
In the post-reionization era, the baryons assembled into the protogalaxies and eventually the present population of the galaxies evolved through merger and evolution. In this work, we discuss a possible probe of the statistical distribution and evolution of the H i density in the post-reionization era. We introduce an estimator of the H i power spectrum from the post-reionization Universe by observing it through the strong gravitational lenses by the nearby galaxy cluster. We also analytically calculate the uncertainties associated with the estimates of the post-EoR power spectrum for the discussed estimator. We access the efficacy of this estimator in the context of 19 galaxy clusters for which the lensing potential has been estimated earlier by various authors. We find that by combining the lensed power spectrum through eight of these cluster lenses, it is possible to estimate the post-reionization H i power spectrum at five-sigma significance for angular multipoles <4000 for a uGMRT observation of 16 MHz bandwidth from redshifts of 1.25, 1.5 with a total of 400 h of observation. With the same setup, for a redshift of 3.0, we need 200 h of total observation time. The estimator also suppresses the diffused galactic foreground, though, the latter is still a dominant contributor to the overall signal and hence need to be estimated and mitigated. We discuss the merits and demerits of the estimator. © 2021 The Author(s) Published by Oxford University Press on behalf of Royal Astronomical Society.